PENINGKATAN HASIL BELAJAR SISWA KELAS III SD NEGERI 1 PEUSANGAN PADA MATERI TEKS NARASI MENGGUNAKAN MEDIA PEMBELAJARAN CROSSWORD PUZZLE BERBASIS DIGITAL - Zahara, Riska; Nurlaili; Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Students learning outcomes regarding narrative texts remain relatively low, making it necessary to use engaging and innovative learning media. This study aims to determine the improvement in students ability to understand narrative text material through the use of digital crossword puzzle learning media among third-grade students at SD Negeri 1 Peusangan, to examine teacher and student activities during instruction using digital crossword puzzle learning media, and to assess students responses to the use of digital crossword puzzle learning media in narrative text instruction. This study employed a qualitative approach using Classroom Action Research (CAR), conducted over two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. Data collection techniques included observation, testing, and documentation. Based on the research findings, it was determined that the use of digital crossword puzzle learning media can improve students ability to understand narrative text material. The results of Cycle I showed a 45% improvement in learning outcomes, and Cycle II yielded a 90% improvement, indicating that student learning outcomes increased by 45%. Regarding teacher activities, Cycle I showed a 74,16% rate, which increased to 97.45% in Cycle II and can be categorized.